OPTIMISING THE DEVELOPMENT OF EXTRACURRICULAR TALENT INTERESTS IN THE MANAGEMENT OF FACILITIES AND INFRASTRUCTURE AT SD NEGERI 2 BATULO - Yurfiah Yurfiah; Kosilah Kosilah; Aulia Nur Afifa Samuin; Defi Selfiana Putri (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This study aims to examine the optimization of student interest and talent development through extracurricular activities and analyze its relationship with the management of facilities and infrastructure at SD Negeri 2 Batulo. The research uses a qualitative approach with a case study method. Data collection was carried out through interviews, observations, and documentation involving the school principal, extracurricular guiding teachers, students, and the school committee. The results of the study indicate that extracurricular activities that are planned and implemented in a structured manner can enhance student participation, develop interest and talent, and shape positive character traits such as discipline, responsibility, and teamwork. Additionally, the optimization of extracurricular activities has an impact on improving the effectiveness of school facilities and infrastructure utilization and maintenance. There is a positive relationship between the development of extracurricular activities and the more optimal management of facilities and infrastructure. Collaboration between the school, teachers, students, and the school committee is a key factor in improving the quality of primary education sustainably.